Effects of Blood Transfusion on the Risk of Hepatitis C Infection in Hemodialysis Patients: A Meta-Analysis - Yuli Astuti; Yulia Lanti Retno Dewi; Bhisma Murti (Masters Program in Public Health, 2020)
Background: It is estimated that 2% of the world's population (about 123 million people) was infected with hepatitis C. Blood transfusion is one of the therapies, but this therapy is at risk of being a transmission me